Allelopathic potential of serjania lethalis: evidence from Sesamum indicum (2015)
This study was designed to test the effect of different fractions of ethanolic extracts of young (y) and mature (m) leaves of Serjania lethalis A. St- Hil (Sapindaceae) on sesame ( Sesamum indicum L.) seedling growth and metaxylem cells. Crude ethanolic extracts were prepared from the powder of young and mature S. lethalis leaves and fractionated by means of column chromatography. For the seedling growth bioassay, sesame seeds germinated at concentrations of 0.8, 0.4 and 0.2 mg mL -1 were used. After seven days, the lengths of the aerial part and of the primary root were measured. The sesame metaxylem cell growth bioassay was performed with seedlings grown in solutions containing the different fractions in the same concentrations as above. The tested fractions (Fy2; Fy3; Fy5 e Fm1) showed inhibitory activity on seedling growth, interfering mainly in root growth. The fraction Fy5 showed similar activity to the one caused by the herbicide Oxyfluorfen. This fraction was also responsible for causing the greatest inhibition of metaxylem cell growth in sesame roots at the concentration 0.8 mg mL -1 . The results permitted to conclude that the different fractions found in the ethanolic extract of S. lethalis young leaves are promising sources of substances with phytotoxic properties